Ecology-Based Regulatory Model for Seagrass Ecosystem Protection in the Aru Islands - Ricky Marthen Wattimena (IHSA Institute, 2026)
Seagrass ecosystems serve important ecological functions as habitats for marine life, coastal protection, and blue carbon sinks. However, seagrass ecosystem protection in the Aru Islands still faces various challenges due to weak coastal area management regulations that are not yet ecologically based. This study aims to analyze the legal regulations for seagrass protection, identify weaknesses in coastal management regulations, and formulate an ecologically based regulatory model for seagrass ecosystem protection in the Aru Islands. The study uses normative legal methods with a legislative and conceptual approach, supported by limited empirical data. The results indicate that seagrass protection regulations in Indonesia are still partial and sectoral, and do not provide specific protection for seagrass ecosystems. Furthermore, coastal area management regulations are still oriented towards natural resource utilization rather than ecological protection. This study proposes an ecologically based regulatory model through an ecoregional approach, strengthening coastal village regulations, community participation, integrated coastal management, and integrating blue carbon governance as an effort to realize sustainable seagrass ecosystem protection in the archipelago